Making the case for enhanced enforcement cooperation between data protection authorities: insights from competition law - Kloza, D.; Mo cibroda, A. (International data privacy law, 2014)
Due to globalization and developments in ICT, data protection authorities (DPAs) increasingly often deal with privacy and data protection breaches of a cross-border nature. Hence, there is a critical need for efficient international enforcement cooperation amongst these authorities. The paper describes the status quo of such cooperation, examines two recent cross-border cases investigated under the current arrangements (the 2012 change of Google's privacy policy and WhatsApp), and analyses provisions on cooperation in two proposed European reforms in the field (the European Union and the Council of Europe). Subsequently, it discusses how the question of enforcement cooperation is addressed in competition law. Finally, building on the experience of competition law, it suggests certain conditions and means for effective cooperation between DPAs.